2004
DOI: 10.1637/7188-033104r1
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of the Nine Serovar Reference Strains of Haemophilus paragallinarum

Abstract: The virulence of the reference strains of the nine currently recognized Kume serovars of Haemophilus paragallinarum was investigated. The capacity of the H. paragallinarum strains to cause the typical clinical signs of upper respiratory tract disease associated with infectious coryza in unvaccinated, nasal-challenged chickens was assessed. Differences in virulence were assessed by means of a standardized scoring system for clinical signs. All nine strains were pathogenic to chickens, producing typical clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…paragallinarum isolates from Uganda are pathogenic to chickens, in agreement with other reports of isolates from elsewhere (Page, 1962;Reid & Blackall, 1984;Sawata et al ., 1985b;Lin et al ., 1996;Bragg, 2002a;Soriano et al, 2004). Using disease scores described by Bragg (2002b), there was no significant variation in the virulence between the isolates in chickens.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…paragallinarum isolates from Uganda are pathogenic to chickens, in agreement with other reports of isolates from elsewhere (Page, 1962;Reid & Blackall, 1984;Sawata et al ., 1985b;Lin et al ., 1996;Bragg, 2002a;Soriano et al, 2004). Using disease scores described by Bragg (2002b), there was no significant variation in the virulence between the isolates in chickens.…”
Section: Discussionmentioning
confidence: 96%
“…It was observed that transformation of the wild-type NAD-dependent serovar C-3 to a NAD-independent variant also decreased its virulence (Taole et al, 2002). Soriano et al (2004) demonstrated variations among the nine reference serovars of the three serogroups of Av. paragallinarum , with serovar C-1 being more virulent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each bird was examined for clinical signs by three experienced observers and the score given to each bird was agreed unanimously by all three observers. The mean daily clinical signs score was calculated as previously reported (22) and differences in the scores were compared using the Student's t-test. Seven days after the challenge, infraorbital sinus swabs from chickens were streaked onto a BHI agar plate supplemented with 5% bovine serum and 0.01% NAD.…”
Section: Methodsmentioning
confidence: 99%
“…Infectious coryza (ICR) is an acute respiratory disease of chicken caused by Haemophilus paragallinarum, a Gram-negative bacterium (Blackall et al 2005;Blackall 1999). ICR induces nasal and lacrimal discharges, facial swelling, and diarrhea reducing the growth and egg production in chicken (Han et al 2016;Soriano et al 2004). Although ICR induces very high morbidity, it has about 1.6% CFR in chicken in Nepal.…”
Section: Infectious Coryzamentioning
confidence: 99%